Real-world Effectiveness of Antipsychotics for the Treatment of Negative Symptoms in Patients with Schizophrenia with Predominantly Negative Symptoms - Novick, Diego; Montgomery, William; Treuer, Tamas; Moneta, Maria Victoria; Haro, Josep Maria (Pharmacopsychiatry, 2017)
This study assessed the comparative effectiveness of antipsychotics in the treatment of patients with schizophrenia presenting with prominent negative symptoms and no-to-mild positive symptoms. Data were taken from a 3-year prospective, international, observational study (n=17 384). This post-hoc study focused on 3 712 patients who started antipsychotic monotherapy and had moderate-to-severe negative symptoms and no-to-mild positive symptoms (Clinical Global Impression-Severity Scale [GGI-SCH]). Patients were classified into 3 treatment cohorts: olanzapine, other atypicals and typicals. Multiple regression analyses were performed. All treatment groups experienced improvement in negative symptoms and social functioning during follow-up. The adjusted mean change in the CGI-SCH negative symptoms scores during follow-up was greater for olanzapine-treated patients by 0.220 (p<0.001) (vs. other atypicals) and by 0.453 (p<0.001) (vs. typicals). Olanzapine-treated patients were also most likely to achieve response of negative symptoms and improvement in social functioning, and to stay on the initial medication longer. Patients with schizophrenia treated with antipsychotics experienced improvement in negative symptoms and social functioning during follow-up. Olanzapine appeared to be more effective compared with other antipsychotics.
Keywords: antipsychotics; negative symptoms; schizophrenia; SOHO